Alteration of the soil bacterial community during parent material maturation driven by different fertilization treatments. (May 2016) - Sun, Li; Xun, Weibing; Huang, Ting; Zhang, Guishan; Gao, Jusheng; Ran, Wei; Li, Dongchu; Shen, Qirong; Zhang, Ruifu
Abstract: Soil parent materials are potential arable land resources that have great value for utilization. Soil bacteria play vital roles in soil formation, and soil parent material provides the basic nutritional environment for the development of the microbial community. Due to the extremely limited available nutrients in most parent materials, fertilization management is important for providing necessary available nutrients and for enhancing the maturation process of the parent materials. After 30 years of artificial maturation driven by different fertilization treatments, the soil development of three different parental materials was evaluated, and the bacterial community compositions were investigated using a high-throughput nucleic acid sequencing approach. The results showed that fertilization management increased the soil fertility and microbial biomass and enhanced soil parent material maturation compared with cultivation alone. Supplying available nutrients via chemical fertilization was more effective than cultivation alone for soil nutrient accumulation, microbial biomass promotion, and copiotrophic bacterial enrichment during soil parent material development. The soil bacterial community structure was determined by both parent material and fertilization strategies. Compared to straw returning, chemical fertilization-driven parent material maturation decreased soil bacterial diversity and significantly changed the soil bacterial community structure. However, compared to chemical fertilization, straw returning had a less negative effect on soil bacterial diversity, but was not as efficient in resolving the nutrient limitation during soil parent material maturation. This study provided insight into the maturation of soil parent materials for agriculture production to support the ever constant need for food by an increasing human population. Highlights: Fertilizations enhanced soil parent material maturation compared with cultivation alone. Chemical fertilization was effective on enriching copiotrophic bacteria during soil maturation. Chemical fertilization decreased soil bacterial diversity and richness during soil maturation. Straw returning has less negative effect on bacterial diversity compared to chemical fertilization.